2016
DOI: 10.4067/s0717-97072016000400012
|View full text |Cite
|
Sign up to set email alerts
|

Denitrogenation by Adsorption of Pyridine on Ni/Support Adsorbents

Abstract: In this work we have carried out the adsorption of pyridine using three different supports (activated carbon, SiO 2 and γ-Al 2 O 3 ). After choosing the best support, due to its higher adsorption capacity, we have impregnated the support with nickel at three different concentrations (2, 4 and 6% w/w) by wet impregnation to study the adsorption of pyridine by π-complexation. All the samples (supports and adsorbents) were characterized by N 2 adsorption-desorption by the BET method and electrophoretic migration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…On this matter, the incorporation of nickel in different porous materials has been widely studied [7,24,25], due to the high adsorption capacity of this metal on diverse pollutants. However, in our previous work [3], we have shown that the incorporation of 4% nickel on alumina decreases the adsorption capacity of pyridine, due to the formation of NiAl 2 O 4 . On the other hand, the incorporation of boron has shown an improvement in the activity of HT catalysts, which is mainly associated with the modification of the acidity and dispersion of the active metals [26,27].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…On this matter, the incorporation of nickel in different porous materials has been widely studied [7,24,25], due to the high adsorption capacity of this metal on diverse pollutants. However, in our previous work [3], we have shown that the incorporation of 4% nickel on alumina decreases the adsorption capacity of pyridine, due to the formation of NiAl 2 O 4 . On the other hand, the incorporation of boron has shown an improvement in the activity of HT catalysts, which is mainly associated with the modification of the acidity and dispersion of the active metals [26,27].…”
Section: Introductionmentioning
confidence: 77%
“…In order to economize the desulfurization or denitrogenation processes, other milder methods must be developed. In this regard, several research groups have studied the elimination of these types of molecules by adsorption [3][4][5][6][7], which, unlike HT reactions, is carried out at ambient temperature and pressure. Despite there being a wide variety of solids used as adsorbents, alumina is one of the main supports used in HT reactions [8][9][10][11][12][13] and has shown the capacity to remove sulfur and nitrogen compounds simultaneously by adsorption, as described by Kim et al [4].…”
Section: Introductionmentioning
confidence: 99%